Reply to the 'Comments on "Dental lessons from past to present: ultrastructure and composition of teeth from plesiosaurs, dinosaurs, extinct and recent sharks"' by H. Botella et al., RSC Adv., 2016, 6, 74384–74388. Issue 11 (19th January 2017) - Luebke, A.; Loza, K.; Patnaik, R.; Enax, J.; Raabe, D.; Prymak, O.; Fabritius, H.-O.; Gaengler, P.; Epple, M.
Abstract : The structure and composition of 13 fossilized tooth and bone samples aged between 3 and 70 million years were analysed. Abstract : The structure and composition of 13 fossilized tooth and bone samples aged between 3 and 70 million years were analysed. It was found that they all contained high amounts of fluoroapatite. This indicates that originally present hydroxyapatite had been converted to fluoroapatite during the diagenesis. Thus, the chemical analysis allows no conclusion with respect to the original composition of our fossil samples. Our results indicate that the diagenetic transformation of hydroxyapatite into fluoroapatite is at least partially dependent on microstructural characteristics of the original tissue such as the degree of porosity.